New insights into the pathogenesis of SARS-CoV-2 during and after the COVID-19 pandemic - Carvajal, Jonatan J.; García-Castillo, Valeria; Cuellar, Shelsy V.; Campillay-Véliz, Claudia P.; Salazar-Ardiles, Camila; Avellaneda, Andrea M.; Muñoz, Christian A.; Retamal-Díaz, Angello; Bueno, Susan M.; González, Pablo A.; Kalergis, Alexis M.; Lay, Margarita K. (Frontiers in Immunology, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the respiratory distress condition known as COVID-19. This disease broadly affects several physiological systems, including the gastrointestinal, renal, and central nervous (CNS) systems, significantly influencing the patient's overall quality of life. Additionally, numerous risk factors have been suggested, including gender, body weight, age, metabolic status, renal health, preexisting cardiomyopathies, and inflammatory conditions. Despite advances in understanding the genome and pathophysiological ramifications of COVID-19, its precise origins remain elusive. SARS-CoV-2 interacts with a receptor-binding domain within angiotensin-converting enzyme 2 (ACE2). This receptor is expressed in various organs of different species, including humans, with different abundance. Although COVID-19 has multiorgan manifestations, the main pathologies occur in the lung, including pulmonary fibrosis, respiratory failure, pulmonary embolism, and secondary bacterial pneumonia. In the post-COVID-19 period, different sequelae may occur, which may have various causes, including the direct action of the virus, alteration of the immune response, and metabolic alterations during infection, among others. Recognizing the serious adverse health effects associated with COVID-19, it becomes imperative to comprehensively elucidate and discuss the existing evidence surrounding this viral infection, including those related to the pathophysiological effects of the disease and the subsequent consequences. This review aims to contribute to a comprehensive understanding of the impact of COVID-19 and its long-term effects on human health.